AI-DRIVEN TOOLS AND DIGITAL PLATFORMS AS A CATALYST FOR PROFESSIONAL COMMUNICATION SKILLS IN IT STUDENTS - Mudra, Olena (Київський національний університет технологій та дизайну, 2026)
The integration of artificial intelligence (AI) and digital platforms into higher education has reshaped the development of professional communication skills, particularly among IT students. This paper explores how AI-driven tools and collaborative digital environments enhance communication competence, foster intercultural interaction, and simulate real-world professional contexts. The study also includes a brief analysis of widely used platforms and tools in IT education. The findings demonstrate that AI technologies significantly contribute to adaptive learning, real-time feedback, and the formation of professional communication strategies. However, challenges such as overreliance on AI and ethical considerations remain critical. In the context of globalization and digital transformation, professional communication has become a core competence for IT specialists. Modern IT professionals are expected not only to possess strong technical skills but also to effectively communicate in multilingual and multicultural environments. The rapid development of AI technologies has significantly influenced educational practices. AI-driven tools and digital platforms provide innovative opportunities for developing communication skills through interactive, personalized, and practice-oriented learning environments. The aim of this study is to analyze the role of AI-based tools and digital platforms in enhancing professional communication skills among IT students and to examine their practical application in higher education.
Keywords: Artificial Intelligence; digital learning; AI-driven tools; IT спеціальності; AI in Education